Education as a Driver to the Demographic Dividend - Anderson Rocha deJesus Fernandes; Bernardo Lanza Queiroz (Microbial Biotechnology)
ABSTRACT Demographic changes, particularly population aging, influence societal and economic development. While often seen as a challenge, aging also presents opportunities through demographic and educational dividends. This commentary discusses how improvements and expansion of education might generate a demographic dividend. Education boosts productivity and well‐being, helping mitigate the economic pressures of aging. However, realising these benefits requires equitable, high‐quality education and labor market reforms to support diverse and aging workforces. Education is pivotal for sustainable development, especially in low‐ and middle‐income countries. It addresses aging‐related challenges, maximises demographic dividends, and fosters long‐term inclusive economic growth.